2016
DOI: 10.1186/s13048-016-0228-9
|View full text |Cite
|
Sign up to set email alerts
|

The serine protease prostasin (PRSS8) is a potential biomarker for early detection of ovarian cancer

Abstract: BackgroundOvarian cancer (OVC) is the deadliest of all gynecologic cancers, primarily as a consequence of asymptomatic progression. The complex nature of OVC creates challenges for early detection, and there is a lack of specific and sensitive biomarkers suitable for screening and detecting early stage OVC.MethodsPotential OVC biomarkers were identified by bioinformatic analysis. Candidates were further screened for differential expression in a library of OVC cell lines. OVC-specific overexpression of a candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…Among the proteins we identified as biomarker candidates for OC some have been discussed previously [ 5 ], such as Mucin-16 (CA125) and Major epididymis-specific protein E4 (HE4), Midkine (MK) [ 16 , 17 ], Kallikrein-11 (hK11) [ 18 ], Folate receptor alpha (FR) [ 19 , 20 ] and Prostasin (PRSS8) [ 21 , 22 ]. Boylan et al [ 5 ] also using PEA technology further reported an association of OC with Interleukin-6 (IL-6) [ 23 25 ], Kallikrein-6 (KLK6) [ 26 ], Furin (FUR) [ 27 ], Chemokine (C-X-C motif) ligand 13 (CXCL13) and Tumor necrosis factor ligand superfamily member 14 (TNFSF14), but none of these proteins were among our top candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Among the proteins we identified as biomarker candidates for OC some have been discussed previously [ 5 ], such as Mucin-16 (CA125) and Major epididymis-specific protein E4 (HE4), Midkine (MK) [ 16 , 17 ], Kallikrein-11 (hK11) [ 18 ], Folate receptor alpha (FR) [ 19 , 20 ] and Prostasin (PRSS8) [ 21 , 22 ]. Boylan et al [ 5 ] also using PEA technology further reported an association of OC with Interleukin-6 (IL-6) [ 23 25 ], Kallikrein-6 (KLK6) [ 26 ], Furin (FUR) [ 27 ], Chemokine (C-X-C motif) ligand 13 (CXCL13) and Tumor necrosis factor ligand superfamily member 14 (TNFSF14), but none of these proteins were among our top candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Mok et al [ 64 ] demonstrated an upregulation of human prostasin (PRSS8) in ovarian cancer cells compared to normal cells, and increased levels of PRSS8 in sera from ovarian cancer patients compared to normal controls. Recent western blot analysis of sera that had been depleted of the highly abundant proteins showed that PRSS8 levels were increased in early stage ovarian cancer samples compared to benign samples or healthy controls [ 65 ]. Our Proseek ® data corroborated these results as we found that PRSS8 is noticeably higher in the sera of women with early and late stage ovarian cancer as compared to healthy women or women with benign ovarian disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hepsin, prostasin, and TMPRSS2 upregulation in epithelial breast, prostate, and ovarian cancer cell lines, mouse models, and patient samples are believed to contribute to increased proliferation, tumor growth, metastasis, ascites formation, and various other invasive processes (107,(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125). Overexpression of hepsin in prostate epithelium in a prostate tumor model (LPB-Tag mice) resulted in increased basement membrane disorganization and tumor metastasis to distant organs, which did not occur in control mice, indicating that hepsin is capable of promoting prostate cancer metastatic processes (119).…”
Section: Activation Of the Matriptase-par-2 Signaling Axismentioning
confidence: 99%